(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The COVID-19 pandemic has posed new and complex challenges to healthcare systems around the world. This article examines the organization of medical rehabilitation for patients infected with COVID-19, the stages of the rehabilitation process, existing problems, and solutions to overcome them. The goal is to improve the quality of life of patients and restore their ability to work through effective medical rehabilitation.